Effect of spin-polarized subbands in the inhomogeneous hole gas providing the indirect exchange in GaMnAs bilayers - Boselli, M. A.; Lima, ICD; Ghazali, A. (Elsevier B.V., 2004)
The magnetic order resulting from the indirect exchange in the metallic phase of a (Ga,Mn)As/GaAs double layer structure is studied via Monte Carlo simulation. The polarization of the hole gas is taken into account, establishing a self-consistency between the magnetic order and the electronic structure. The Curie-Weiss temperatures calculated for these low-dimensional systems are in the range of 50-80 K, and the dependence of the transition temperature with the GaAs separation layer is established. (C) 2003 Published by Elsevier B.V.
Keywords: diluted magnetic semiconductor; (Ga,Mn)As; spintronics